2002
DOI: 10.1152/ajpheart.2002.282.1.h122
|View full text |Cite
|
Sign up to set email alerts
|

Activated polymorphonuclear cells increase sickle red blood cell retention in lung: role of phospholipids

Abstract: This study investigates the role of the activated polymorphonuclear cell (APMN) products on sickle red blood cell (SRBC) retention/adherence in the pulmonary circulation. Isolated rat lungs were perfused with (51)Cr-labeled normal RBCs (NRBC) or SRBCs (10% hematocrit) suspensions +/- PMNs. Specific activities of lung and perfusate were measured and retention (the number of SRBC/g lung) was calculated. SRBC retention was 3.5 times greater than NRBC retention. PMN activation was required to increase SRBC retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 60 publications
(67 reference statements)
2
33
0
Order By: Relevance
“…54 Although the adhesion of platelets and leukocytes to activated endothelial P-selectin [55][56][57] should have been blocked by the mAb combination that included anti-PSGL-1 mAb, it is possible that other P-selectin recognition determinants such as sulfatides 58 or glycoprotein Ib-IX-V 59 may have mediated the adhesion of nonerythroid cells to P-selectin on endothelial cells. Platelet activating factor (PAF) could have mediated the adhesion of sickle RBCs, [60][61][62] but the differences between the responses of P-selectin-deficient and wild-type mice suggest that a PAF effect was not a major one. We cannot exclude the possibility that TSP might have contributed to the changes we observed.…”
Section: Discussionmentioning
confidence: 99%
“…54 Although the adhesion of platelets and leukocytes to activated endothelial P-selectin [55][56][57] should have been blocked by the mAb combination that included anti-PSGL-1 mAb, it is possible that other P-selectin recognition determinants such as sulfatides 58 or glycoprotein Ib-IX-V 59 may have mediated the adhesion of nonerythroid cells to P-selectin on endothelial cells. Platelet activating factor (PAF) could have mediated the adhesion of sickle RBCs, [60][61][62] but the differences between the responses of P-selectin-deficient and wild-type mice suggest that a PAF effect was not a major one. We cannot exclude the possibility that TSP might have contributed to the changes we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Human neutrophils were isolated according to a previous report ( 56 ). All protocols utilizing human neutrophils were approved by the Medical College of Wisconsin Institutional Review Board.…”
Section: Pma-induced Hocl Formation By Human Neutrophilsmentioning
confidence: 99%
“…The zileuton concentrations used were based on previous findings reported by Guidot et al (14), Haynes and Obiako (16), and studies performed in our laboratory demonstrating a 50% reduction of leukotriene B 4 at 2.5 M and a 95% reduction of leukotriene B4 at the 50 M in A-23187-stimulated whole blood from individuals with sickle cell anemia. The effect of zileuton on SRBC PS externalization was assessed based on a previous study (16), which demonstrated that zileuton attenuates AN mediated retention/adherence of SRBCs in isolated perfused lung.…”
Section: Specific Protocolsmentioning
confidence: 99%
“…In isolated perfused lung, products of activated neutrophils (ANs) further enhanced SRBC retention/adherence. This effect of ANs on RBC adhesion is attenuated when neutrophils are pretreated with a 5-lipoxygenase inhibitor (16). Whereas these in vitro results suggest the involvement of leukotriene products, the cellular mechanism involved in neutrophil-mediated increased SRBC adhesion to EC has yet to be elucidated.…”
mentioning
confidence: 93%